Pengajaran Bahasa Inggris Berbasis Sekolah Alam Di RT03/RW01 Kelurahan Tuahmadani Kecamatan Tampan Pekanbaru - Syaifullah Syaifullah; Refika Andriani (Asosiasi Dosen Akuntansi Indonesia, 2022)
English Vocabulary Mastery of Children in RT03/RW01 Tuahmadani, Tampan District of Pekanbaru is low. It could be seen from daily activity, interaction between researcher and the children during preliminary research. Moreover, it was seen from the quiz result, 55 (Very Poor). There are two main causes had by them; some do not study english yet, and some do not like English. As the way out of those two causes, researcher had provided Teaching English Natural Based in several meetings. There were several concepts of Teaching English Natural Based: First, teaching English any time and anywhere, the material can delivered in door or outdoor. Second, Teaching English by model, teacher must be as model in teaching process. The last, Learning by doing is as a based. As a result, after teaching the children by using Natural Based, their English or vocabulary has little improvement. In short, the children are happy in studying English by using Natural Based and supported by simple media.